Load Frequency Control of Multi-Area Multi-Source System Using Social Spider Optimized Controllers - Debashish Bhowmik, Pushpa Gaur (International Journal of Advanced Science and Technology, 2020)
A load frequency control scheme is presented in this article for a three area diverse-source system. An individual area comprises of three generating units, viz. thermal system with single reheat turbine, hydro system with electric governor, and gas turbine power plants. The application of a fractional order controller called Tilt-Integral-Derivative (TID) controller is used for secondary control in all the control areas. The various parameters of the controllers are individually optimized using Social Spider Optimization. The dynamic responses of TID are compared with those of classical controller in the presence and absence of generation rate constraint (GRC). The comparisons reveal superior performance of TID over classical controller in both the condition in terms of time of settling down of transient and peak deviations. The performance of the system with TID and PID are also tested using random load perturbation (RLP) as disturbance by replacing step load perturbation. Analysis also proves that TID controller works superior to classical controller for RLP also.